Overview of Stress During Work and Study from Home Reviewed from the Academic Community and Mulawarman University Students - Lisda Sofia; Muhammad Sultan; Muhammad Khairul Nuryanto; Dina Lusiana Setyowati; Fergie Fernando Hesfi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Large-scale social restriction policies during the Covid-19 pandemic. demands that all societies reduce interaction with each other. However, the existing changes have caused a lot of pressure, especially in the field of education, among universities. The existing pressure is a source of stress for education workers and students. The purpose of this study was to find out the picture of stress during work and study from home. The subjects involved were 746 people, including the academic community and students at Mulawarman University. The findings found that 43% consisted of an age range of 20-24 years. Age has a weak correlation to WFH and LFH stress. The majority of 389 female respondents had moderate stress levels. Gender is not correlated with stress during WFH and SFH. that the level of education has a weak negative relationship with stress. The majority of job status as students have WFH and SFH stress. Employment status is negatively correlated weakly to WFH and SFH stress. At the level of education as many as 316 people have moderate stress. Employment status is negatively correlated weakly to WFH and SFH stress. The final analysis showed that body mass index had no relationship with WFH and SFH stress. Abstrak: Kebijakan pembatasan sosial berskala besar di masa pandemi Covid-19. menuntut semua masyarakat mengurangi interaksi satu sama lain. Akan tetapi perubahan yang ada menimbulkan banyak tekanan khususnya dalam bidang pendidikan, di kalangan perguruan tinggi. Tekanan yang ada menjadi sumber stres bagi tenaga pendidikan dan pelajar. Tujuan penelitian ini adalah untuk mengetahui gambaran stres selama bekerja dan belajar dari rumah. Subjek yang terlibat sebanyak 746 orang, merupakan civitas akademik dan mahasiswa di Universitas Mulawarman. Hasil temuan didapatkan bahwa 43% terdiri dari rentang usia 20-24 tahun. Usia memiliki korelasi yang lemah terhadap stres WFH dan LFH. 389 responden perempuan mayoritas memiliki tingkat stres sedang. Jenis kelamin tidak berkorelasi dengan stres selama WFH dan SFH. bahwa tingkat pendidikan memiliki hubungan negatif yang lemah dengan stres. Mayoritas status pekerjaan sebagai mahasiswa memiliki stres WFH dan SFH. Status pekerjaan berkorelasi negatif lemah terhadap stres WFH dan SFH. Pada tingkat pendidikan sebanyak 316 orang memiliki stres sedang. Status pekerjaan berkorelasi negatif lemah terhadap stres WFH dan SFH. Analisis terakhir menunjukkan bahwa indeks masa tubuh tidak memiliki hubungan dengan stres WFH dan SFH.